Activin suppresses the expression of inflammatory genes and signaling proteins in human leukemia monocytic THP-1 cells: Activin inhibits expression of inflammatory genes - Yun, Sang Oh; Kim, Young Il; Ahn , Hyung Joon; Min, Sun Young (Cellular and Molecular Biology, 2023)
Activin regulates inflammation, cell proliferation, immune response, wound repair, and endocrine function. In this study, we investigated the effect of activin on inflammatory genes in THP-1 cells and the involvement of NF-κB, AKT, and mitogen-activated protein kinase (MAPK) signaling. Cell viability was determined using a colorimetric assay with the MTS/PES solution. The mRNA levels were analyzed using reverse transcription-quantitative polymerase chain reaction. The expression of NF-κB, AKT, and MAPK signaling proteins was measured using immunoblot analysis. Activin A did not affect THP-1 cell viability at concentrations below 50 ng/ml. Activin decreased the mRNA expression of cytokines (interleukin (IL)-1β, IL-6, and tumor necrosis factor-α (TNF-α), toll-like receptor 4 (TLR4), and matrix metallo-proteinases (MMP)-9 proteins but did not affect IL-8 expression. Activin increased the expression of TLR2 and MMP-2. In addition, activin inhibited the phosphorylation of NF-κB p65, AKT, and MAPK (c-Jun N-terminal kinase (JNK), extracellular signal-regulated kinase (ERK), and p38 MAPK) signaling proteins. Our results suggest that activin may be involved in anti-inflammation by inhibiting inflammatory gene expression and regulating NF-κB and AKT/MAPK signaling.